2014
DOI: 10.1590/s0004-28032014000200004
|View full text |Cite
|
Sign up to set email alerts
|

GENDER-RELATED DIFFERENCES IN CLINICAL COURSE OF CROHN’S DISEASE IN AN ASIAN POPULATION: a retrospective cohort review

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…23 The authors also showed that, in general, women with CD received IBD -specific medications less frequently, with the phenomenon of no treatment in IBD also being noted more often among female patients. 23 Furthermore, in a retrospective Asian cohort study, Law et al 24 reported a delayed use of immunosuppressive therapy women treated with TNF inhibitors in our study cannot be explained by a lower prevalence of CD in this population.…”
mentioning
confidence: 45%
“…23 The authors also showed that, in general, women with CD received IBD -specific medications less frequently, with the phenomenon of no treatment in IBD also being noted more often among female patients. 23 Furthermore, in a retrospective Asian cohort study, Law et al 24 reported a delayed use of immunosuppressive therapy women treated with TNF inhibitors in our study cannot be explained by a lower prevalence of CD in this population.…”
mentioning
confidence: 45%
“…The higher prevalence of smoking, as one of the most consistently studied environmental factors of IBD, in males compared with females might have contributed to the higher mortality rate in male patients. 29 Alternatively, some studies point to the influence of hormones on the brain-gut-microbiota axis as the reason for sex differences in IBD prognosis, but the mechanism underlying this complex pathophysiology is still not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian populations, although prevalence of smoking is increasing, it remains less than it is in Europe [16] . Recent studies demonstrated an increased risk of complications in smokers compared to non-smokers in Hong Kong [17] and the need for surgery in Korea [18] .…”
Section: Impact Of Current Smoking On the Ibd Coursementioning
confidence: 99%